Respuesta :
y = m x + b
2 = 6 m + b
-4 = 8 m + b /*(-1 )
---------------------------
2 = 6 m + b
+
4 = - 8 m - b
--------------------
6 = - 2 m
m = - 3
2 = 6 * ( - 3 ) + b
2 = - 18 + b
b = 20
The equation is:
y = - 3 x + 20 ( or in the other form: 3 x + y - 20 = 0 )
2 = 6 m + b
-4 = 8 m + b /*(-1 )
---------------------------
2 = 6 m + b
+
4 = - 8 m - b
--------------------
6 = - 2 m
m = - 3
2 = 6 * ( - 3 ) + b
2 = - 18 + b
b = 20
The equation is:
y = - 3 x + 20 ( or in the other form: 3 x + y - 20 = 0 )